(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The evaluation of frozen semen quality is an essential aspect in determining male fertility for artificial insemination programs. This study aims to evaluate the characteristics of Friesian Holstein (FH) bull-frozen semen in different classes (proven and unproven) based on protein profiling and molecular evaluation. Materials and Methods: This study used frozen semen straws from FH bulls selected according to criteria for proven (6 individuals) and unproven (6 individuals) bulls produced by the Singosari AI Center (AIC). Sperm motility parameters were assessed using Computer Assisted Semen Analysis (CASA Supervision®, Germany), while sperm viability and abnormality were evaluated through eosin-nigrosin staining under a microscope at 400´ magnifications. The integrity of the sperm plasma membrane was determined using the hypoosmotic swelling test, and acrosome integrity was analyzed using the fluorescein isothiocyanate PNA-propidium iodide staining method. Protamine deficiency was quantified using Chromomycin A3 fluorescence staining, while DNA fragmentation was assessed using the acridine orange technique. Results: The findings demonstrated that there were no statistically significant differences (p > 0.05) in the assessed parameters of frozen semen quality between FH-proven and unproven bulls. Furthermore, in FH-proven bulls, a negative correlation was observed between protamine deficiency and acrosome integrity (r = −0.528) and between protamine deficiency and sperm DNA fragmentation (r = −0.467). The parameters of protamine deficiency in unproven bulls exhibited a positive correlation with sperm progressive motility. Conclusion: The frozen semen quality of FH bulls in different classes (proven and unproven) was found to be equally good. Molecular-based analysis allows for a more accurate determination of semen quality. These findings are significant for bull breeding stations when comprehensively evaluating semen quality. J. Adv. Vet. Anim. Res., 11(3): 796-802, September 2024 http://doi.org/10.5455/javar.2024.k831